2020
DOI: 10.1017/s1751731119002532
|View full text |Cite
|
Sign up to set email alerts
|

Genetic parameters for haemoglobin levels in sows and piglets as well as sow reproductive performance and piglet survival

Abstract: Genetic parameters were estimated for haemoglobin (Hb) levels in sows and piglets as well as sow reproductive performance and piglet survival. Reproductive traits were available between 2005 and 2014 for 7857 litters from 1029 Large White and 858 Landrace sows. In 2012 and 2013, Hb levels, sow BW and sow back fat depth were measured on 348 sows with 529 litters 5 days prior to farrowing. In addition, Hb levels were available for 1127 one-day-old piglets from 383 litters (a maximum of three piglets per litter) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
6
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 20 publications
5
6
2
Order By: Relevance
“…For GL, there were some differences among different populations. Zhang et al [2] and Hollema et al [22] estimated heritabilities of 0.14 and 0.21, respectively, which were slightly lower than the results in our study; and the heritability estimated by Hanenberg et al [24] was consistent with this study. However, due to the small phenotypic variation in GL, the possibility of improving the reproductive performance of sows by changing the gestation cycle was also reduced.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…For GL, there were some differences among different populations. Zhang et al [2] and Hollema et al [22] estimated heritabilities of 0.14 and 0.21, respectively, which were slightly lower than the results in our study; and the heritability estimated by Hanenberg et al [24] was consistent with this study. However, due to the small phenotypic variation in GL, the possibility of improving the reproductive performance of sows by changing the gestation cycle was also reduced.…”
Section: Discussionsupporting
confidence: 90%
“…In this study, the estimated heritabilities of seven reproductive traits ranged from 0.09 to 0.26. Heritabilities for TNB and NBA were in the range reported in previous studies, for instance, Wolf et al [21] estimated heritabilities of 0.13 for TNB and 0.14 for NBA in a Czech Large White pig population, Zhang et al [2] estimated that the heritabilities of both traits were 0.13, and Hollema et al [22] estimated that the heritability for NBA was 0.11, which were slightly higher than our estimated heritabilities. Furthermore, our estimates of heritabilities were larger than those from Ye et al [11], who reported estimated heritabilities for these two traits of 0.07 and 0.06, respectively.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Lactate concentration was measured from 0.8 to 22 mmol/L; higher values were classified as 23 mmol/L. The Hemocue® Hb 201 Analyzer (Hitado GmbH, Möhnesee, Germany) was used to measure haemoglobin concentration [ 21 ]. The measuring scale runs from zero to 15.9 mmol/L.…”
Section: Methodsmentioning
confidence: 99%
“…Lactate concentration was measured from 0.8 to 22 mmol/L; higher values were classi ed as 23 mmol/L. The Hemocue Hb 201 Analyzer was used to measure haemoglobin concentration (21). The measuring scale runs from zero to 15.9 mmol/L.…”
Section: Data Collectionmentioning
confidence: 99%